Bilateral prefrontal rTMS and theta burst TMS as an add-on treatment for depression: A randomized placebo controlled trial. (January 2015) - Prasser, Julia; Schecklmann, Martin; Poeppl, Timm B.; Frank, Elmar; Kreuzer, Peter M.; Hajak, Goeran; Rupprecht, Rainer; Landgrebe, Michael; Langguth, Berthold
Abstract Objectives. Repetitive transcranial magnetic stimulation (rTMS) of the left dorsolateral-prefrontal cortex (DLPFC) exerts antidepressant effects. In this randomised controlled clinical trial we aimed to test the safety and therapeutic efficacy of bilateral theta-burst stimulation (TBS) as an add-on therapy to standard treatment of major depression. Methods. Fifty-six patients diagnosed with a moderate to severe depressive episode received 15 daily treatments of either rTMS (110% motor-threshold; rightDLPFC, 1000 stimuli at 1 Hz + leftDLPFC, 1000 stimuli at 10 Hz), theta-burst stimulation (80% motor-threshold; rightDLPFC, continuous TBS, 1200 stimuli + leftDLPFC, intermittent TBS, 1200 stimuli), or sham TMS (N = 17, sham coil with the TBS protocol). Results. There was no significant effect in the primary outcome measures (change of the 21-item Hamilton Rating Scale for Depression). However, there was a tendency towards an increased responder rate at the end of the follow-up period for both active treatments as compared to sham, and this tendency was most pronounced for the TBS group. Conclusions. This pilot study did not reveal significant advantages of bilateral TBS or rTMS over sham treatment as an add-on treatment for major depression. A tendency towards a superior effect of bilateral TBS at the end of the follow-up period may warrant further studies.